Re-thinking the possibility of the urban roof space - Lu, Ke (School of Architecture, Planning and Geomatics, 2016)
Within an. urban context, if multiple level thinking associated with landscape architectural design principles are applied to roof spaces, these can be activated for specific purposes. The space on top of roofs has the potential to be converted into areas for production, recreation , socializing and even for healing. Today, in the urban context it is difficult to find spare spaces that can be actively used by people; most public squares focus on improving the micro-economy, leaving almost no space for recreation. Also, within the urban context many buildings are designed in an "unfriendly manner" creating dark and damp spaces on ground level where people are not willing to stay. These kinds of dark, damp and "un-friendly" environments are not beneficial to people. Because people are looking for recreational spaces in an urban environment, the recreational, multi-purpose use of roof spaces is becoming necessary. There are many examples within the urban context of people trying to use roof space for the growing of vegetables, or creating gardens for biodiversity purposes. Currently many green roofs only focus on increasing the ecological value of the space, a seemingly simple function , causing many people to lose interest in the concept. Landscape architects should not only work on ground level but on multiple levels within the urban environment. James Corner who designed the "High Line Project" worked on an abandoned bridge, activating the dead space and thus allowing the space to be used for human activity and at the same time improving the urban ecology. Urban hospitals require a comfortable environment for their patients, who can benefit from the right kind of healing environment. Roof spaces have the potential to be used for this purpose. When designing a roof space, landscape architects should not only focus on the ecological and cultural aspects, but also focus on space making for a specific group of people (patients). Creative ways of re thinking the healing landscape environment and bringing healing landscape principles and ideas while applying them to a completely artificial environment is the challenge.